Building SMEs competitive advantage in export markets: the role of human capital and relationship quality - Md. Daud Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Small businesses look for cooperative relationships with foreign partners to build competitive advantage in export markets. In addition, the ability of small businesses to compete is also strongly related to human capital specifically the managerial competences. This study aims to investigate the effect of managerial competences on the relationship quality, which in turn affects the competitive advantage of small business in export markets. Data were collected among small and medium manufacturers. A total of 228 small and medium businesses participated in this study. This study employs structural equation modelling approach for data analysis. The findings indicate that human capital is a function of relationship quality and competitive advantage. In addition, relationship quality is significantly related to competitive advantage. Finally, relationship quality partially mediates the relationship between human capital and competitive advantage. At the end of this paper, the conclusion and discussion are presented, and limitation and future study are discussed.